Encouraging brand attachment on consumer behaviour: Pet-friendly tourism segment - Alves, H.; Sousa, B.; Carvalho, A.; Santos, V. R.; Dias, Á.; Valeri, M. (Journal of Tourism, Heritage and Services Marketing, 2022)
Purpose: The aim of this paper is to study the factors that influence consumer behaviour through brand attachment, in the pet-friendly segment in Portugal. Pet-friendly tourism has stood out as a very recognized and valid tourism and marketing segment, growing worldwide, urging the complex needed advances on tourism practices performance. Methods: The application of the model to a group of 190 respondents carried out in order to analyse the relationships between brand attachment, trust, satisfaction, commitment, loyalty and quality of service. To test our measurement model, data was analysed using the SmartPLS 3.2. Results: Results reveal that quality of the service, satisfaction, trust and commitment had a strong relationship with the loyalty of the respondents. As for the brand attachment, the variables that showed the most influence were satisfaction, trust and commitment. Implications: The research still needs to be empirically applied in pet-friendly tourism settings to enrich their robustness in a cross-cultural tourism experiences, covering a wider spread of abroad tourism destinations and products. This study thus contributes to a better clarity at the theoretical level of brand attachment and consumer behaviour, as well as making it possible to understand from the consumers' side, which characteristics are part of their decision-making process, granting relevant data that can cooperate in the definition of better marketing strategies.